2021
DOI: 10.3390/polym13111877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photoinitiator on Precursory Stability and Curing Depth of Thiol-Ene Clickable Gelatin

Abstract: Recent advances highlight the potential of photopolymerizable allylated gelatin (GelAGE) as a versatile hydrogel with highly tailorable properties. It is, however, unknown how different photoinitiating system affects the stability, gelation kinetics and curing depth of GelAGE. In this study, sol fraction, mass swelling ratio, mechanical properties, rheological properties, and curing depth were evaluated as a function of time with three photo-initiating systems: Irgacure 2959 (Ig2959; 320–500 nm), lithium pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…However, at present, the most commonly used photocrosslinking initiator, Irgacure 2959 (I2959), is oxygen-sensitive and requires the airtight protective barriers. Moreover, to activate I2959, UV light is potentially damaging to cellular DNA, and the gelation reaction with I2959 is slower than that with the ruthenium compound used as a photoinitiator in this study 48 . UV irradiation of cells generates reactive oxygen species (ROS), which causes cytotoxicity.…”
Section: Discussionmentioning
confidence: 90%
“…However, at present, the most commonly used photocrosslinking initiator, Irgacure 2959 (I2959), is oxygen-sensitive and requires the airtight protective barriers. Moreover, to activate I2959, UV light is potentially damaging to cellular DNA, and the gelation reaction with I2959 is slower than that with the ruthenium compound used as a photoinitiator in this study 48 . UV irradiation of cells generates reactive oxygen species (ROS), which causes cytotoxicity.…”
Section: Discussionmentioning
confidence: 90%
“…Next, Holmes et al reported that the concentration of the photoinitiator used for preparation of poly(ethylene glycol) and collagen-based hydrogels affected their swelling properties, storage modulus and the cytotoxicity towards selected cell lines [ 18 ]. The impact of the type of the photoinitiator used during the hydrogel synthesis was additionally confirmed by Yang et al [ 19 ].…”
Section: Introductionmentioning
confidence: 70%
“…Gelatin is one of the most studied biomaterials as it is well characterized, biodegradable and water-soluble [ 46 ]. The pka values of the acidic components of the polymers and the pH of the buffer medium used for the swelling of the hydrogel might play a significant role in the determination of the swelling behavior of the hydrogel.…”
Section: Discussionmentioning
confidence: 99%